V.18 N. 1 INDICATORI DI BENESSERE ANIMALE NELLA SPECIE BOVINA E RIFLESSI PRATICO-APPLICATIVI IN SANITA’ PUBBLICA VETERINARIA (Rassegna di Diritto, Legislazione e Medicina Legale Veterinaria, 2021)
The authors examine animal welfare indicators for the bovine species, with particular reference to dairy cow. This work proposes a practical approach to the Functional Area of Animal Health, considers the issue of animal welfare as an integrated concept, the current legislation –horizontal and vertical-, the epidemic surveillance system (Classyfarm) and biosecurity in breeding.
Keywords: law, indicators, animal welfare, bovine species, dairy cow, Veterinary Public Health, Animal Health, epidemic surveillance system, biosecurity.